FRI0185 Autologous stem cell transplantation international scleroderma trial. (1st June 2001) - Van Laar, JM; Farge, D; Tyndall, A
Abstract : Background: Autologous hemopoietic stem cell transplantation (HSCT) is emerging as a potential therapy for severe rheumatic autoimmune diseases, including systemic sclerosis. Phase I/II studies involving 65 patients with progressive SSC and organ involvement proved the feasibility of HSCT and demonstrated significant longterm effects on skin score, but with considerable toxicity including a treatment-related mortality of 12%. These results must be viewed against current data on morbidity and mortality (5-yr survival 50%) for this patient category. At the recent EBMT/EULAR consensus meeting, the concept for a randomised, controlled trial was approved to investigate whether the longterm benefits of HSCT outweigh the risks. As a result the ?ASTIS Trial? (Autologous Stem cell Transplantation International Scleroderma Trial) has now been launched. Objectives: To compare efficacy and safety of HSCT versus monthly intravenous pulse-therapy cyclophosphamide in patients with diffuse systemic sclerosis and heart, lung or kidney involvement at risk for premature mortality. The goal of both treatments is to prolong survival by arresting or retarding the disease process. It is postulated that HSCT has superior efficacy, which needs to be balanced against potentially higher toxicity. Methods: The ASTIS Trial is an international, multicenter, prospective, controlled, randomised, phase III study in selected patients with early diffuse SSC and major organ involvement. The ASTIS Trial is conducted under the auspices of EBMT/EULAR (Basel, Switzerland). The investigational treatment arm (HSCT) comprises the following consecutive steps: mobilisation of hematopoietic stem cells with i.v. cyclophosphamide (2 × 2 gr/m 2 ) and filgrastim (10 ug/kg/day), leukapheresis and selection of CD34 + stem cells, conditioning with i.v. cyclophosphamide (200 mg/kg) and rbATG (7.5 mg/kg), followed by reinfusion of autologous stem cells. The control treatment arm consists of 12 monthly i.v. pulses cyclophosphamide (750 mg/m 2 ). The primary endpoint is event-free survival during the study period of 2 years, events defined as the development of persistent major organ failure (heart, lung, kidney) and death. Secondary endpoints include treatment-related mortality, toxicity, skin score, SHAQ, and quality-of-life. Side studies include evaluation of immune reconstitution in blood and fibrotic activity in skin. It is intended to enrol 200 patients in 3 years. Results: Conclusion: The ASTIS Trial is the first randomised study to evaluate the potential clinical benefits of HSCT versus conventional therapy in severe rheumatic autoimmune disease. The study will address whether a short period of intense immune suppression differs from chronically given, more moderate immune suppression, bot qualitatively and quantitatively. Given the low incidence of severe forms of systemic sclerosis, and the efforts needed to conduct the study, international collaboration is mandatory.